Respuesta :

Answer:

2x( 2x-1) (x+3)

Step-by-step explanation:

4x^3 + 10x² - 6x

Factor out 2x

2x( 2x^2 +5x -3)

Factor inside the parentheses

2x( 2x-1) (x+3)

Answer:

2x(2x-1)(x+3)

Step-by-step explanation:

4x³ + 10x² - 6x

  • 4x³ = 2x²×(2x)
  • 10x² = 5x×(2x)
  • 6x   = 3×(2x)

here 2x is a common factor then we can pull it out:

4x3 + 10x² - 6x = 2x²×(2x) + 5x×(2x) - 3×(2x)

                        = 2x(2x² + 5x - 3)

                        = 2x(2x-1)(x+3)

2x² + 5x - 3 = (2x-1)(x+3) , here you can use the quadratic formula to find the roots.